JURIDICAL REVIEW OF AGREEMENTS PROVIDING BANKING LOANS (CREDIT) TO INDIVIDUAL CUSTOMERS IN THE FORM OF GENERAL RURAL CREDIT (KUPEDES) - Gultom, Sarles; Sinaga, Merry Natalia; Caronina Sitepu, Desy Kartika; Maujana Saragih, Sepri Ijon; Utami, Fikha Syra (Faculty of Law, Universitas Pekalongan, 2024)
This article discusses the important role of the financial system, especially the People's Business Credit (KUPEDES) program, in supporting economic development in Indonesia, especially for Micro, Small, and Medium Enterprises (MSMEs). KUPEDES is designed to improve access to capital for rural communities that often have difficulty in meeting formal credit requirements. This program contributes to poverty alleviation and encourages local economic growth. With a clear legal framework, KUPEDES protects the rights and obligations of banks as credit providers and customers as credit recipients. The dispute resolution mechanism regulated by the OJK provides legal certainty, increasing customer confidence in applying for credit. However, challenges remain, especially in ensuring customer understanding of credit terms and risks. Therefore, it is important for financial institutions to provide adequate education on the legal dimensions of credit agreements. Implementation of training and counseling programs can help customers manage their finances wisely. Overall, KUPEDES is not only a tool to improve access to capital, but also a driver of financial inclusion that strengthens the rural economy and supports sustainable growth in Indonesia. An in-depth analysis of the legal aspects of the KUPEDES agreement is essential to ensure compliance and sustainability of rural economic development through financial inclusion.